Ethical issues from interoperability in electronic health records - Chasiotis , I.; Chasioti, E. Z. (Bioethica, 2022)
The adoption of electronic systems in healthcare through Information Systems Technologies (ICT) has led to an increase in the quality of health care provided, the creation, collection, transfer and storage of healthcare data as well as their retrieval by authorized health professionals. The use of ICT leads to the reduction of medical errors, the reduction of costs, the immediate retrieval of data at any time and at any point and finally to the satisfaction of patients. The transfer of patients between different health care providers leads to the need for electronic means of recording examinations and reports so that they can be retrieved whenever necessary. The interoperability of information systems with each other for timely access to patient information such as Personal Electronic Patient Record (AHFY) containing information such as history, diagnoses, medical and imaging examinations is considered necessary for data security. However, many ethical challenges arise such as the confidentiality of data traffic, access control and retrieval, invasion of privacy, storage, preservation and distribution of data. The discussion and recommendations that should take place concern the informed consent of patients and the right to autonomy, the security of personal data through the General Regulation of Personal Data (GDPR-Law 2016/679), Quality Assurance and planning safe and integrated interoperability of healthcare systems and how they can be addressed.